Digital Hate Narratives: A Pragmatic Study of Insulting Comments across Social Media - Kencana, Nila; Utami, Elva; Sartika, Dewi; Anwar, Eka Nurdianty (Corolla International Conference, 2025)
This study investigates the pragmatic strategies used by netizens to construct insulting comments across three major social media platforms: Facebook, TikTok, and Instagram. Employing a qualitative research design, the study analyzes 60 publicly available comments collected from viral posts related to public figures and controversial topics. Using theoretical frameworks from speech act theory, impoliteness theory, and Gricean pragmatics, the research identifies multiple forms of verbal aggression, including bald-on-record insults, sarcasm, mock politeness, and presupposition-based attacks. The findings reveal that each platform exhibits distinct patterns of linguistic hostility shaped by its design, user culture, and interactional norms. Facebook fosters extended and confrontational discourse, TikTok promotes brief and performative sarcasm, while Instagram favors stylized and indirect expressions. Additionally, the study demonstrates that insults in digital contexts function not only as expressions of offense but also as performative acts of identity, judgment, and group alignment. This research contributes to digital pragmatics by showing how classical linguistic theories operate in technologically mediated environments. It also offers practical insights for content moderation, digital literacy, and ethical communication in online spaces.